The true applicability of indefeasibility of title in the Malaysian Torrens System in relation to section 340 of the National land code 1965 / Faridah Saman - Saman, Faridah (Faculty of Law, 2007)
The highest court in Malaysia, the Federal Court, has ruled in favor of immediate indefeasibility for the Malaysian Torrens system on the issue in Adorn Properties. There has been previous decision of the Federal Court on the subject matter of indefeasibility involving forgery. The pertinent question which arises is whether this decision is correct in light of the legislative framework laid down in section 340 of the Malaysian National Land Code 1965. If so, it would certainly bring about the demise of the doctrine of deferred indefeasibly under the Malaysian Torrens system. Public confidence in the Torrens system depends upon the rock-solid effect of registration. This public faith is reinforced by the indefeasibly concept which serves as a shield to protect most attacks on title. Indefeasibly is the fundamental feature of the Torrens system which save the persons dealing with the registered proprietors from the trouble and expense of going behind the Register.